Can Consumers Distinguish Persistent from Transitory Income Shocks? - Jeppe Druedahl; Thomas H. Joergensen (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2018)
We study whether households can distinguish persistent from transitory income shocks, and the implications for consumption-saving behavior. We construct a novel consumption-saving model where the household must infer the persistent component of its income process from actual income realizations together with an additional noisy private signal. We first show that the degree of imperfect information has important consequences for the interpretation of transmission parameters to persistent and transitory income shocks. A large transitory transmission parameter can e.g. be estimated despite of a low marginal propensity to consume because the short run covariance between income growth and consumption growth increases when households cannot distinguish persistent from transitory income shocks. We further show that the households' degree of knowledge can be identified from panel data on income and consumption. Finally, we estimate a high degree of knowledge in the Panel Study of Income Dynamics.
Keywords: D11; D12; D15; D31; D83; E21; 330; Consumption; Saving; Income Shocks; Learning; Consumer Information